Tauroursodeoxycholic acid partially prevents apoptosis induced by 3-nitropropionic acid - Rodrigues, CMP (2015)
Ursodeoxycholic acid (UDCA) has been shown to be a strong modulator of the apoptotic threshold in both hepatic and nonhepatic cells. 3-Nitropropionic acid (3-NP), an irreversible inhibitor of succinate dehydrogenase, appears to cause apoptotic neuronal ce